Impact of water pH on haematology and serum enzyme activities in Schizothorax richardsonii (Gray) - Kapila, Rajeev; Kapila, Suman; Basade, Yasmeen (Indian Journal of Fisheries, 2011)
Haematological characteristics in fish changes in response to environmental conditions and thus could serve as indicators of sub lethal environmental stress. Exposure of snow trout, Schizothorax richardsonii to different water pH (5.0-9.0) for 24 h resulted in alteration in haematological and enzymological parameters. The fishes showed obvious signs of stress at pH 5.0 as indicated by their behavioural changes. Blood haemoglobin (Hb), red blood cells (RBC) andpacked cell volume (PCV) were higher at both extremes of pH, but significantly (p